Morphological evolution of a macrotidal back‐barrier environment: The Amazon Coast. Issue 7 (8th June 2020) - McLachlan, Robin L.; Ogston, Andrea S.; Asp, Nils E.; Fricke, Aaron T.; Nittrouer, Charles A.; Schettini, Carlos A. F.
Abstract: Coastal barriers provide sheltered, low‐energy settings for fine‐grained sediment deposition and retention, although the process of back‐barrier infilling and how tidal‐channel connectivity impacts this process is not well‐understood. Understanding how back‐barrier environments infill and evolve is necessary to predict how they will respond to future changes in sea‐level and sediment supply. With this motivation, in situ observations and sedimentary signatures from an Amazonian tidal‐channel system are interpreted to create a conceptual model of morphological evolution in a macrotidal back‐barrier environment that is rich in fine‐grained sediment, vegetated by mangroves and incised by tidal channels with multiple outlets. Results indicate that within a high‐connectivity back‐barrier channel, tidal processes dominate sedimentation and morphological development. Sediment cores (<60 cm) exhibited millimetre‐scale tidalites composed of sand and mud. High‐connectivity channels allow tidal propagation from multiple inlets, and in this case, the converging flood waves promote delivery of sediment fluxing through the system to the mangrove flats in the convergence zone. Sediment preferentially deposits in regions with adequate accommodation space and dense vegetation, and in these zones, sediment grain size is slightly finer than that transiting through the system. The greatest sediment‐accumulation rates (3 to 4 cm yr −1 ), calculated from steady‐state 210 Pb profiles, were found in the convergence zone near the mangrove‐channel edge. As tidal flats aggrade vertically and prograde into the channels, accommodation space diminishes. In effect, the channel's narrowest stretch is expected to migrate along the path of net‐sediment flux towards regions with more accommodation space until it reaches the tidal‐convergence zone. The location of recent preferential infilling is evidenced by relatively rapid sediment‐accumulation rates, finer sediment and significant clustering of small secondary tidal channels. These findings shed light on how sediment transported through vegetated back‐barrier environments is ultimately preserved and how evidence preserved in surface morphology and the geological record can be interpreted.